Struktur Formula dan Ekpresi Formulaik dalam Tradisi Mamaca di Kabupaten Bondowoso - Ahmad Rifa’i (SULUK: Jurnal Bahasa, Sastra, dan Budaya, 2020)
The objective of this research are describing about: formula and formulaic expression Mamaca tradition in Bondowoso. This research is descriptive-qualitative research. The research data sources are (1) the process of Mamaca, (2) informant, and (3) documentation. The research result showed, the formula which is obtained in Mamaca tradition, are line connection and poetry concept formula. Formulaic expressions are translating process of tokang tegges and poetry concept based on rhyme and purwakanthi.